Evaluation Of Surface Water Quality of Samples from Some Archaeological Cities in Northeastern Libya (Comprehensive Journal of Science, 2025)
The purpose of this study was to evaluate water quality in three different locations in northeastern Libya and was done by the assessment of some physiochemical and microbiologicalparameters. The chemical evaluation focused on parameters that indicates water qualityincluding pH, alkalinity, heavy metal contamination, and conductivity. Additionally,biological status of these samples has been evaluated. The warning signs provided byauthorities in the ancient city of Shahat indicated that Ain Apollo water is not potable.However, no more details were given specifying whether it is chemical, microbial, or othertypes of pollution. Because of the historical importance of the ancient Libyan cities, we choseto collect samples from three cities including Tolmeitha (Ptolemais), Benghazi(Hesperides/Berenice originally Euesperides), and Shahat (Cyrene). Results show that thelead metal exceeded the local and international limits. However, other metals includingcadmium, nickel, copper, and iron were in the acceptable range. No acid rain was found inTolmeitha, and the pH levels for the surface water samples were acceptable. As forbacteriological analysis, there was no indication for the presence of Total Coliform (T.C.F),Escherichia Coli (E.Coli), and Streptococcus Faecalis bacteria.
Keywords: Water quality, physio-chemical parameters, environmental evaluation, surface water pollution, Lethe River, Ain Apollo